Antibacterial Effect of Calabash (Crescentia Cujete) Leaf and Fruit Extract on Preservation of Lettuce (Lactuca Sativa) Leaves with Escherichia Coli - Isabella T. Magno; Rheeza P. Esmail; Maira Shariz S. Lim; Jasmine Nikki Jen D. Padua; Keziah L. Reyes; Lanz Alfred G. Tugom; Anamarie G. Valdez; Hassanal P. Abusama (Universitas Pendidikan Indonesia (UPI), 2022)
This study was carried out to determine the antibacterial effect of Calabash Leaf and Fruit Extracts on the preservation of lettuce affected with Escherichia coli. Additionally, this was done to assess the following: change in length of lesion on lettuce leaves depending on the effectiveness of the different concentrations of treatments; and significant difference of the extracts. The experimental research design was employed in which 2 set-ups were prepared by setting Calabash Leaf Extract and Calabash Fruit Extract. Each set-up has 3 treatments with different concentrations. The antibacterial activity of different concentrations of extracts was evaluated after 3 days of observation through interpreting the change in the size of the 1 mm purposively-made lesion on lettuce leaves. The investigations were focused on the damaged part measured. t-test results revealed that the t-value calculated was smaller than the critical value at a 5% level of significance, thus the difference is not significant. These findings revealed that the Calabash extracts equally possess a high antibacterial effect against Escherichia coli. The Calabash Leaf and Fruit Extracts can potentially be considered as an alternative tool to prevent plant-tissue deterioration and to prolong the shelf life of crops and vegetables.